Bio-treatment of effluent from anaerobically digested urban organic waste using microalgae (Chlorella sorokiniana) - Lee, Zi Xiong. (2012)
This report provides a detailed research and experiment on the removal of nutrients from synthetic wastewaste, which has similar composition and properties like the effluent from anaerobically digested urban organic waste, using microalgae and also the harvesting of the microalgae biomass by chitosan flocculation. Utilization of microalgal culture offers a better solution for the removal of the nutrients as compare to biological nitrogen removal process as it does not require a desirable C/N ratio and the operation cost is much more afford to implement for poorer countries. The harvested microalgae biomass by chitosan coagulant provides a product with great variety of uses as compare to chemical coagulant that produces large amount of sludge that can only be disposed into the landfill. However the author feels that the solutions to harvest the microalgae can be more economically and environmentally improve, especially on the use of chitosan as the coagulant during the flocculation process. Therefore the present study focuses on determining the parameter such as pH and ratio of chitosan to microalgae for optimal removal efficiency.